SARS-CoV-2 associated ischemic stroke: first case report in Peru - Mariños, Evelyn (2020)
The disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is known as Coronavirus Disease 2019 (COVID-19). Its involvement is mainly respiratory, but various neurological manifestations have been described. The neurotropism and potential neuropathotogenic role of SARS-CoV-2 is based on animal models and cases of neurological condition described in other coronaviruses, as well as recent reports of specific neurological syndromes related to COVID-19, including ischemic stroke. The Spanish Society of Neurology described ischemic stroke as the second most frequent neurological manifestation in patients with COVID-19. Likewise, the state of hyperinflammation and blood hypercoagulability triggered by COVID-19 would increase the risk of prothrombotic events. We report 3 cases of peruvian patients who presented ischemic stroke associated with COVID-19: we describe the clinical manifestations, paraclinical examinations and review the world literature.